2017
DOI: 10.4236/jdm.2017.74019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Underlying Increase of the Serum Magnesium Concentration Observed Following Treatment with Sodium-Glucose Cotransporter 2 Inhibitors

Abstract: Aim: The EMPA-REG OUTCOME study reported that the sodium-glucose cotransporter 2 inhibitor (SGLT2-i) suppressed cardiovascular (CV) events in patients with type 2 diabetes; we recently suggested that increase of the serum magnesium (Mg) by SGLT2-i's can, in part, explain this reduction. The objective of this study was to elucidate the mechanism underlying the elevation of the serum Mg level induced by treatment with SGLT2-i's. Methods: We analyzed the data of 37 patients with type 2 diabetes who underwent clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Clinical trials have demonstrated their effectiveness in reducing hospitalizations due to heart failure, slowing the progression of chronic kidney disease, and decreasing major cardiovascular events, with consistently lower mortality rates [ 1 ]. Recent evidence suggests a class effect of SGLT2 inhibitors, with randomized controlled studies revealing a significant elevation in serum magnesium levels, ranging from 0.04-0.1 mmol/L, in patients with type 2 diabetes, regardless of baseline hypomagnesemia [ 2 , 3 ]. However, the role of SGLT2 inhibitors in treating hypomagnesemia in non-diabetic patients remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have demonstrated their effectiveness in reducing hospitalizations due to heart failure, slowing the progression of chronic kidney disease, and decreasing major cardiovascular events, with consistently lower mortality rates [ 1 ]. Recent evidence suggests a class effect of SGLT2 inhibitors, with randomized controlled studies revealing a significant elevation in serum magnesium levels, ranging from 0.04-0.1 mmol/L, in patients with type 2 diabetes, regardless of baseline hypomagnesemia [ 2 , 3 ]. However, the role of SGLT2 inhibitors in treating hypomagnesemia in non-diabetic patients remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The potential link between hypomagnesemia and glucose intolerance, especially in the context of diabetes mellitus, warrants further investigation. SGLT2 inhibitors, established for their role in diabetes management, are associated with a significant increase in serum magnesium concentration among diabetic patients [ 2 ]. This intriguing connection highlights the potential of SGLT2 inhibitors not only for glycemic control, but also as contributors to magnesium balance.…”
Section: Introductionmentioning
confidence: 99%
“…We recently suggested that the increase of the serum Mg level associated with SGLT2 inhibitor treatment could explain, at least in part, the reduction of the CV risk observed in the EMPA-REG OUTCOME study [13], because, as mentioned above, hypomagnesemia increases the risk of CV events. We and another group reported that patients with hypomagnesemia are more likely to enjoy the beneficial effects of SGLT2 inhibitor treatment on the risk of CV events, because elevation of the serum Mg was found to be more likely to occur in patients with low serum Mg levels at the baseline [14,15]. …”
Section: Mg Concentration Increases With Sglt2 Inhibitor Treatmentmentioning
confidence: 99%